2020
DOI: 10.1192/j.eurpsy.2019.12
|View full text |Cite
|
Sign up to set email alerts
|

Self-stigma in serious mental illness and autism spectrum disorder: Results from the REHABase national psychiatric rehabilitation cohort

Abstract: Background. Self-stigma is a major issue in serious mental illness (SMI) and is negatively associated with patient outcomes. Most studies have been conducted in schizophrenia (SZ). Less is known about self-stigma in other SMI and autism spectrum disorder (ASD). The objectives of this study are: (i) to assess the frequency of self-stigma in a multicentric nonselected psychiatric rehabilitation SMI and ASD sample; and (ii) to investigate the correlates of elevated self-stigma in different SMI conditions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 65 publications
1
31
0
Order By: Relevance
“…This concurs with findings in serious mental illness where self-stigma has been associated with reduced capacity for intimacy and more negative parenting experiences (61). Self-stigma has been found to affect one in five people with ASD (7,62). It has been associated with poorer recovery-related outcomes (i.e., reduced self-esteem and well-being and higher depression and suicide risk) (7).…”
Section: Access To Adequate Healthcaresupporting
confidence: 83%
See 3 more Smart Citations
“…This concurs with findings in serious mental illness where self-stigma has been associated with reduced capacity for intimacy and more negative parenting experiences (61). Self-stigma has been found to affect one in five people with ASD (7,62). It has been associated with poorer recovery-related outcomes (i.e., reduced self-esteem and well-being and higher depression and suicide risk) (7).…”
Section: Access To Adequate Healthcaresupporting
confidence: 83%
“…Self-stigma has been found to affect one in five people with ASD ( 7 , 62 ). It has been associated with poorer recovery-related outcomes (i.e., reduced self-esteem and well-being and higher depression and suicide risk) ( 7 ). Gender-diverse autistic individuals are confronted with multiple sources of stigma (e.g., intersection of ASD and gender identity stigma) and may be at particular risk of self-stigma ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For ethical purposes, we have chosen a stepped wedge cluster randomized trial design, with a waiting list type control condition. Previous research from the French national REHABase network showed that (i) most patients were dissatisfied with their interpersonal relationships at the time of admission and asked for interventions improving social function [36] and (ii) elevated self-stigma was frequent (31.2% of the 738 participants [37]) and was negatively associated with recovery-related outcomes. Self-stigma has been negatively associated with patient's longitudinal outcomes and to lower benefits from psychiatric rehabilitation [38].…”
Section: Designmentioning
confidence: 99%